Peran Guru Pendidikan Agama Islam Dalam Menanamkan Nilai-Nilai Religius Pada Siswa SMP Muhammadiyah 1 Gatak Program Khusus - Fitriyan, Yassir Hafidh; Salim, Hakimuddin (Jayapangus Press, 2025)
Islamic Religious Education (PAI) has an important role in shaping the character and morals of students. PAI teachers as educational agents are not only in charge of delivering teaching materials, but also act as role models who guide students in spiritual, social, and ethical aspects. This study aims to analyze the role of PAI teachers in instilling students' religious values, the challenges faced, and the strategies applied in learning the supporting and inhibiting factors in the internalization process. The research method used is qualitative with a phenomenological approach. Data were collected through observations, interviews, and literature studies relevant to the role of teachers in Islamic education. Data analysis used Miles and Huberman interactive analysis in the form of data reduction, data presentation and drawing conclusions. The results showed that PAI teachers act as educators, mentors, and motivators in learning. Teachers are required to have pedagogical, personality, social, and professional competencies to create an effective learning environment. In addition, the challenges faced by PAI teachers include low student interest in learning, uncontrolled influence of technology, and limited learning facilities. To overcome these challenges, PAI teachers apply character-based learning strategies, contextual approaches, and technology integration in learning. Supporting factors for the cultivation of religious values are the support of the academic community, a conducive school environment and the role of parents. While the inhibiting factors are the lack of seriousness of students, time constraints and the role of parents. This study concludes that the role of PAI teachers is very significant in building students' morals and character, especially in instilling students' religious values.